2016
DOI: 10.1016/j.juro.2015.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Noctural Enuresis as a Risk Factor for Falls in Older Community Dwelling Women with Urinary Incontinence

Abstract: Purpose-To determine the association between urinary symptoms, fall risk and physical limitations in older community-dwelling women with urinary incontinence (UI).Materials and Methods-In-depth assessment of day and nighttime urinary symptoms, fall risk, physical function, physical performance tests and mental function in older communitydwelling women with UI and who had not sought care for their urinary symptoms. All assessments were performed in the participants' homes. We used univariable and multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…Neither severity of UI nor severity of nocturia was associated with an increased risk of falls, but there was a statistically significant association between nocturnal enuresis and impairment of physical function and the presence of frailty. However, in the multivariable regression model, which included age, physical function, and the frequency of nocturnal enuresis episodes, only physical function remained as significant risk factor for falls . One study, a prospective cohort study of older men in the United States of America, identified a statistically significant association between straining to void and falls, with a 60% increase in falls risk for those reporting the need to push or strain to initiate urination at least half the time …”
Section: What Is Known About the Association Between Falls And Luts?mentioning
confidence: 99%
See 1 more Smart Citation
“…Neither severity of UI nor severity of nocturia was associated with an increased risk of falls, but there was a statistically significant association between nocturnal enuresis and impairment of physical function and the presence of frailty. However, in the multivariable regression model, which included age, physical function, and the frequency of nocturnal enuresis episodes, only physical function remained as significant risk factor for falls . One study, a prospective cohort study of older men in the United States of America, identified a statistically significant association between straining to void and falls, with a 60% increase in falls risk for those reporting the need to push or strain to initiate urination at least half the time …”
Section: What Is Known About the Association Between Falls And Luts?mentioning
confidence: 99%
“…However, in the multivariable regression model, which included age, physical function, and the frequency of nocturnal enuresis episodes, only physical function remained as significant risk factor for falls. 26 One study, a prospective cohort study of older men in the United States of America, identified a statistically significant association between straining to void and falls, with a 60% increase in falls risk for those reporting the need to push or strain to initiate urination at least half the time. 27 The use of sedative medications has been identified as a potential risk factor for falls in those with LUTS.…”
Section: Association Between Falls and Luts?mentioning
confidence: 99%
“…When analyzing the occurrence of previous falls and the risk of falls, no significant difference was found when comparing the study groups. In the literature, the association between UI and falls in older people is well reported [7][8][9] . Possible causes involve extrinsic factors, such as the urgency to get to the bathroom at night 8 and intrinsic factors such as the weakening of PFMs 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the association between UI and falls in older people is well reported [7][8][9] . Possible causes involve extrinsic factors, such as the urgency to get to the bathroom at night 8 and intrinsic factors such as the weakening of PFMs 24 . However, falls are likely consequences of several factors besides UI 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation